ANALISIS KINERJA KEUANGAN BANK BUMN PERIODE 2019-2020 DENGAN METODE RGEC - Salsabila Fildza Alifa (2022)
BUMN (State Owned Enterprises) are-an agency in which all or at least 51% (51%) of its capital is divided into shares owned by the Unitary State of the Republic of Indonesia with the main objective of seeking profit. Banks or PT. The controlling interest in the company or the equivalent interest in State-Owned Enterprises (BUMN) is a bank whose form of business is a Limited Liability Company with 51% shares must be controlled by the state. A healthy bank is a bank that can carry out its duties well. To protect the trust of the public, it is necessary to carry out good bank health management by maintaining bank liquidity. The purpose of this research is to carry out-analysis-ratio-liquidity, profitability ratio, ratio-solvency Bank-BUMN and conduct an assessment-performance-finance-Bank-BUMN-with value interpretation-ratio-in accordance-Bank Indonesia regulations. From the research that has been done using Method-RGEC-At State-Owned Banks in 2019-2020, we get the result that ifseen from the Risk Profile Component (Risk Profile) Bank Negara has 2 metrics, namely credit risk and liquidity risk, each of which is in a "healthy" condition from 2019 to 2020, seen from the GCG component shows BUMN Banks in a "very healthy" condition , and Judging from the component of Capital (Capital) State-Owned Banks during 2019-2020 consecutively are in a "very healthy" state.